2022
DOI: 10.3390/ani12040463
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Albendazole Bioavailability with Menbutone Administration in Sheep

Abstract: The pharmacokinetic interaction between a benzimidazole (albendazole, ABZ) and a choleretic drug (menbutone, MEN) was evaluated in sheep. The plasma disposition of albendazole sulfoxide (ABZSO, active metabolite) and albendazole sulfone (ABZSO2, inactive metabolite) was investigated following an oral administration of albendazole (ABZ) (5 mg/kg) alone or with menbutone (MEN) (intramuscular, 10 mg/kg). Blood samples were collected over 3 days post-treatment, and drug plasma concentrations were measured by high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 50 publications
(85 reference statements)
0
3
0
Order By: Relevance
“…The aryl methyl ether containing an easily hydrolyzed ester group and decarboxylated β-ketoester structural unit ( 1by ) afforded the corresponding phenol in 55% yield . Furthermore, a methyl ester of the choleretic drug menbutone ( 1bz ) as a derivative of 1-methoxynaphthalene resulted in a moderated yield of 40%. It is evident that the hydrolysis of aryl ethers developed in this study offers a unique transformation in organic transformations and pharmaceutical intermediate modification.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The aryl methyl ether containing an easily hydrolyzed ester group and decarboxylated β-ketoester structural unit ( 1by ) afforded the corresponding phenol in 55% yield . Furthermore, a methyl ester of the choleretic drug menbutone ( 1bz ) as a derivative of 1-methoxynaphthalene resulted in a moderated yield of 40%. It is evident that the hydrolysis of aryl ethers developed in this study offers a unique transformation in organic transformations and pharmaceutical intermediate modification.…”
Section: Results and Discussionmentioning
confidence: 99%
“…However, poor solubility is a limitation of the use of benzimidazole antihelmintics. Yet, different pharmaceutical strategies and technologies are available and under discussion to overcome this issue and enhance the oral bioavailability of these drugs in the future . Moreover, the antiviral activity of OBZ has already been reported against human herpesvirus 8 (EC 50 = 1.5 μM) and Zika virus (EC 50 = 0.7 μM), pointing to its broad-antiviral spectrum that is highly desirable for treating remerging and emerging viruses …”
Section: Discussionmentioning
confidence: 99%
“…The choleretic properties of menbutone, increasing bile secretion to intestine, may be used to favor the absorption of compounds with poor water solubility. For instance, it has been shown that this drug has significantly augmented the absorption of the anthelmintic metabolite albendazole sulphoxide from the intestinal lumen in sheep ( 16 ). Menbutone would act in a similar way as a fatty meal in healthy human subjects.…”
Section: Discussionmentioning
confidence: 99%